Frontiers and hotspot evolution in research on Alzheimer’s disease and hypertension: a bibliometric analysis from 2004 to 2023 - Liu, Wenying; Zhao, Yaya; Rao, Yutong; Wu, Zijing; Peng, Yun; Gong, Lianggeng (Frontiers in Neurology, 2025)
BackgroundAlzheimer’s disease (AD) is a neurodegenerative disease that imposes a heavy burden on patients and their families. Hypertension is an important risk factor for AD, but the specific mechanism of its impact is still unclear. This study thus aimed to analyze the relationship and trend changes between AD and hypertension through bibliometric methods.MethodsLiterature on AD and hypertension was retrieved from the Web of Science Core Collection (WoSCC) database between 2004 and 2023. Data regarding countries, institutions, authors and journals were sourced from WoSCC. CiteSpace and VOSviewer were used for data visualization, including author collaboration, timelines view of references, reference bursts and overlay visualization maps of keywords. Excel 2018 software was used for the statistical analysis.ResultsA total of 1,833 publications were ultimately included. From 2004 to 2023, the number of publications per year basically showed an increasing trend. The United States (United States) not only had the largest output of publications and the highest H-index but also had the seven highest frequencies of publication institutions. Kehoe, Patrick ranked first with the most articles among 9,330 authors. The journal with the most published articles was the Journal of Alzheimer’s Disease. Reference analysis revealed a hotspot in the exploration of the pathophysiological association between AD and hypertension. Second, the treatment effects and potential risks of antihypertensive drugs (AHDs) on AD are also the focus of research. Researchers have carried out a series of studies ranging from basic research to clinical research on AHDs for the treatment of AD. Finally, personalized treatment strategies will also become one of the hotspots of future research. Controlling hypertension through lifestyle changes and medication interventions in AD patients is a promising strategy. The analysis of keywords revealed that “amyloid deposition,” “preeclampsia,” “Corona Virus Disease 2019 (COVID-19)” and “biomarkers” have been research hotspots in recent years.ConclusionBy analyzing the references and keywords, we summarized the hot topics and research trends in this field. These findings provide useful information for researchers to explore the relationship between hypertension and AD further, with the hope of providing more effective treatments for AD patients to delay disease progression and improve quality of life.